Prolactin-Producing Pituitary Carcinoma, Hypopituitarism, and Graves’ Disease—Report of a Challenging Case and Literature Review - Bettencourt-Silva, Rita; Pereira, Josué; Belo, Sandra; Magalhães, Daniela; Queirós, Joana; Carvalho, Davide (Frontiers in Endocrinology, 2018)
Introduction: The diagnosis of pituitary carcinoma is very rare, requires the evidence of metastatic disease and has a poor overall survival. Malignant prolactinoma frequently requires dopamine agonist therapy, pituitary surgery, radiotherapy and even chemotherapy. Case description: A 19-year-old female presented with galactorrhea, primary amenorrhea and left hemianopsia. Complementary study detected hyperprolactinemia and a pituitary macroadenoma with cavernous sinus invasion and suprasellar growth. She was treated with cabergoline and bromocriptine without clinical or analytical improvement. Resection of the pituitary lesion was programmed and a non-contiguous lesion of the nasal mucosa was detected during the approach. This metastasis led to the diagnosis of prolactin-producing pituitary carcinoma. After partial resection, the patient was submitted to radiotherapy for residual disease with persistent symptoms. She developed growth hormone deficiency, central hypothyroidism, hypogonadism and permanent diabetes insipidus. Six years later she was admitted for the suspicion of secondary adrenal insufficiency and thyrotoxicosis. Physical findings, laboratory data, thyroid ultrasound and scintigraphy achieved the diagnosis of Graves’ disease and hypocortisolism. She was treated with hydrocortisone and methimazole, but central hypothyroidism recurred after antithyroid drug withdrawal. Nine years after the diagnosis of a pituitary carcinoma, she maintains treatment with bromocriptine, has a locally stable disease, with no metastases. Conclusion: This report highlights an unusual presentation of a prolactin-producing pituitary carcinoma in a young female. The patient had multiple hormone deficiencies due to a pituitary lesion and treatments. The posterior development of hyperthyroidism and adrenal insufficiency brought an additional difficulty to the approach.